Histocompatibility and Immunogenetics in Cord Blood Transplantation - Pablo Rubinstein; Christopher Hillyer (Biological Research, 2010)
This review of the immunogenetics of cord blood transplantation attempts to highlight the connections between classical studies and conclusions of the tissue transplantation field as a scholarly endeavor, exemplified by the work of Professor Hoecker, with the motivations and some recent and key results of clinical cord blood transplantation. The authors review the evolution of understanding of transplantation biology and find that the results of the application of cord blood stem cells to Transplantation Medicine are consistent with the careful experiments of the pioneers in the field, from the results of tumor and normal tissue transplants, histocompatibility immunogenetics, to cell and molecular biology. Recent results of the National Cord Blood Program of the New York Blood Center describe the functioning in cord blood transplantation of factors, well known in transplantation immunogenetics, like the Fl anti-parent effect and the tolerance-like status of donors produced by non-inherited maternal HLA antigens. Consideration of these factors in donor selection strategies can improve the prognosis of transplantation by characterizing "permissibility" in HLA-incompatible transplantation thereby increasing the probability of survival and reducing the likelihood of leukemic relapse.